2010
DOI: 10.1210/en.2009-1048
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor-Dependent Activation of Endothelial Nitric Oxide Synthase in Vascular Endothelial Cells: Role of Phosphatidylinositol 3-Kinase/Akt Pathway

Abstract: The mechanisms of testosterone-induced vasodilatation are not fully understood. This study investigated the effect of testosterone on nitric oxide (NO) synthesis and its molecular mechanism using human aortic endothelial cells (HAEC). Testosterone at physiological concentrations (1-100 nm) induced a rapid (15-30 min) increase in NO production, which was associated with phosphorylation and activation of endothelial NO synthase (eNOS). Then, the involvement of the androgen receptor (AR), which is abundantly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 33 publications
8
73
0
Order By: Relevance
“…101 We recently demonstrated that testosterone rapidly induces NO production via AR-mediated activation of eNOS in human aortic ECs. 89 Furthermore, we showed that AR directly interacts with the p85 subunit of phosphatidylinositol 3-kinase, resulting in phosphorylation/activation of Akt/eNOS signaling. Taking together with our preliminary observation about the involvement of extracellular signal-regulated kinase 1/2 signaling and [Ca2+]i in AR-dependent eNOS activation, quite similar signaling pathways to those for estrogen can be proposed for testosterone (Figure 1), although some of these pathways should be verified in further studies.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 89%
See 1 more Smart Citation
“…101 We recently demonstrated that testosterone rapidly induces NO production via AR-mediated activation of eNOS in human aortic ECs. 89 Furthermore, we showed that AR directly interacts with the p85 subunit of phosphatidylinositol 3-kinase, resulting in phosphorylation/activation of Akt/eNOS signaling. Taking together with our preliminary observation about the involvement of extracellular signal-regulated kinase 1/2 signaling and [Ca2+]i in AR-dependent eNOS activation, quite similar signaling pathways to those for estrogen can be proposed for testosterone (Figure 1), although some of these pathways should be verified in further studies.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 89%
“…Indeed, androgen receptor (AR) has been shown to be expressed in these cells. [89][90][91] Effects of testosterone on animal models of atherosclerosis and neointima formation It has been demonstrated that the administration of testosterone in castrated male rabbits that were fed a high-cholesterol diet reduced aortic atherosclerosis, largely independent of plasma lipids. 92,93 In addition, neointima formation after coronary balloon injury in swine was increased by castration and was reversed by testosterone replacement.…”
Section: Direct Effects Of Testosterone On Vascular Wallsmentioning
confidence: 99%
“…NO is a potent vasodilator that can be synthesised by NO synthase (NOS) and is released by the vascular endothelium, among other tissues, and NO-induced vasodilation is often therapeutically targeted in hypertension and angina (Miller & Megson 2007). In vitro, cultured human endothelial cells increase NO synthesis in response to physiological concentrations of testosterone via nongenomic activation of intracellular signalling pathways and Ca 2C influx (Goglia et al 2010, Yu et al 2010, Campelo et al 2012. Moreover, increased endothelial NOS (eNOS) expression and phosphorylation were observed in testosterone-and DHT-treated human umbilical vein endothelial cells (HUVECs) stimulated with hydrogen peroxide to induce senescence (Ota et al 2012).…”
Section: Vascular Mechanisms Of Testosteronementioning
confidence: 99%
“…In addition to slower acting gene regulation, rapid AR activation of intracellular signalling pathways has also been suggested. Yu et al (2010) described how the rapid phosphorylation of eNOS or NO production was abolished by pre-treatment with an AR antagonist, nilutamide, or by transfection with AR siRNA and that DHT also stimulated eNOS phosphorylation in human aortic endothelial cells (HAECs). The authors suggest that the activation of PI3-kinase/Akt intracellular signalling pathway and the direct interaction of the AR with p85a (the regulatory subunit of PI3-kinase) were responsible for the observed effects (Yu et al 2010).…”
Section: Potential Signalling Mechanisms Of Testosterone In Vascular mentioning
confidence: 99%
“…These cells express ARs and are targets for androgen action 1) . Regarding ECs, it has been reported that androgens rapidly induce nitric oxide (NO) production in human endothelial cells via the phosphorylation/activation of endothelial nitric oxide synthase (eNOS) and that the activation of eNOS is inhibited by an antiandrogen drug or AR knockdown [58][59][60][61][62] . Yu et al demonstrated that testosterone induces the rapid assembly of a membrane-signaling complex among AR, c-Src, and caveolin-1, which facilitates activation of the c-Src/phosphoinositide-3-kinase (PI3K)/serine/threonine protein kinase (Akt) cascade, with the consequent activation of eNOS in vascular ECs 58) .…”
Section: Androgen -Ar System Regulates Vascular Remodelingmentioning
confidence: 99%